Conceptualizing and measuring psychological resilience: What can we learn from physics? - Den Hartigh, Ruud; Hill, Yannick (New ideas in psychology, 2022)
The number of resilience conceptualizations in psychology has rapidly grown, which confuses what resilience actually means. This is problematic, because the conceptualization typically guides the measurements, analyses, and practical interventions employed. The most popular conceptualizations of psychological resilience equate it with the ability to (1) resist negative effects of stressors, (2) “bounce back” from stressors, and/or (3) grow from stressors. In this paper, we review these three conceptualizations and argue that they reflect different concepts. This is supported by important lessons from engineering physics, where such concepts are clearly differentiated with precise mathematical underpinnings. Against this background, we outline why psychological resilience should be conceptualized and measured in terms of the process of returning to the previous state following a stressor (i.e., bouncing back). By establishing a clearer language of resilience and related processes, measurements and interventions in psychological research and practice can be targeted more precisely.
Gesehen am 11.05.2022